2021
DOI: 10.3390/app11167715
|View full text |Cite
|
Sign up to set email alerts
|

The Study on Internal Flow Characteristics of Disc Filter under Different Working Condition

Abstract: A disc filter (DF) is an important component in a micro irrigation system. However, it has a high head loss and low filtration efficiency, which can lead to the inoperability of micro irrigation systems. To improve the filtration ability and to decrease the pressure loss of the irrigation system, it is necessary to internalize the hydraulic characteristics of DFs. In this study, the filter bed of a DF was divided into three parts, i.e., upper, middle, and lower, which were wrapped with a transparent film. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Although numerous studies have explored the factors influencing filter performance, few have comprehensively considered the interactions among multiple factors [27][28][29][30][31]. By introducing interaction terms, this study not only unveils the complex relationships The different combinations of lines in Figure 11 represent different optimal solutions obtained by adjusting parameters through model algorithms when applying the response surface method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous studies have explored the factors influencing filter performance, few have comprehensively considered the interactions among multiple factors [27][28][29][30][31]. By introducing interaction terms, this study not only unveils the complex relationships The different combinations of lines in Figure 11 represent different optimal solutions obtained by adjusting parameters through model algorithms when applying the response surface method.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have explored the factors influencing filter performance, few have comprehensively considered the interactions among multiple factors [27][28][29][30][31]. By introducing interaction terms, this study not only unveils the complex relationships among these factors but also enhances the predictive accuracy of the model.…”
Section: Discussionmentioning
confidence: 99%
“…A high head loss and low filtration efficiency resulting from an uncleaned filter may cause a reduction in the performance of the MIS. (Chi et al, 2021). According to Fernando et al (2020) the most common problem reported by the farmers for MIS usage in coconut plantations was frequent line breakdown and the regular examination of lines for damages.…”
Section: Availability Of Essential Components and Routine Maintenancementioning
confidence: 99%